Pemikiran KH. Abdul Wahid Hasyim Tentang Pendidikan Islam dan Relevansinya Terhadap Pendidikan Islam Kontemporer - Permana, Dian; Siregar, Maragustam; Kusmayadi, Yudi; Firmansyah, Firdaus (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
Islamic education is a process of individual formation based on Islamic teachings. In Islamic education we involve the basic basic elements of the Koran and Hadith. Furthermore, changes and developments in Islamic educational institutions among traditionalists are almost never touched upon, although similarities are found between traditional educational institutions and institutions developed by modernists. (first) to find out KH Abdul Wahid Hasim's thoughts on Islamic education and (second is to find out the relevance of KH Abdul Wahid Hasim's thoughts on contemporary Islamic education. qualitative research method with the type of library research and the data was collected using